2017
DOI: 10.1016/j.ijom.2017.02.393
|View full text |Cite
|
Sign up to set email alerts
|

Third molar surgery outcomes: a comparison between intravenous sedation and general anaesthetic

Abstract: than the surgical removal group (19.75 ± 7.89 min; P < 0.05). Incidence of early postoperative complications were low in both groups. Incidence of transient inferior alveolar nerve injury was 2.3% in the surgical removal group. Incidence of early postoperative infection was 2.3% in the germectomy group. Conclusion: Delaying the removal of impacted mandibular third molars until a problem developed, subjects the patient to unnecessary pain, more complex and costly operations with higher risk for postoperative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The aim of this study was to evaluate changes in the psychoemotional state of patients by removing four wisdom teeth in a single procedure using general anesthesia and sedation techniques. A previous study in New Zealand, Ong, Tong et al [12] also addressed a similar topic in which patients with GAG showed greater preoperative anxiety compared with SG patients. Compared to the present study, significantly higher preoperative results were recorded in GAG, assessing only fear of tooth extraction, while in other questionnaires, the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The aim of this study was to evaluate changes in the psychoemotional state of patients by removing four wisdom teeth in a single procedure using general anesthesia and sedation techniques. A previous study in New Zealand, Ong, Tong et al [12] also addressed a similar topic in which patients with GAG showed greater preoperative anxiety compared with SG patients. Compared to the present study, significantly higher preoperative results were recorded in GAG, assessing only fear of tooth extraction, while in other questionnaires, the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…After evaluating the patient's anxiety, preferences, medical history and the number of teeth to be removed, the most appropriate method of anesthesia is selected for the procedure [11]. Often, out of great fear, patients express a desire to have their teeth removed using sedation or general anesthesia rather than local anesthesia [12]. Sedation is usually more popular than general anesthesia because patients tend to choose this method at first place [13].…”
Section: Introductionmentioning
confidence: 99%